Evaluating quality of life in frailty: applicability and clinimetric properties of the SarQoL® questionnaire. Issue 2 (28th February 2021) - Geerinck, Anton; Locquet, Médéa; Bruyère, Olivier; Reginster, Jean‐Yves; Beaudart, Charlotte
Abstract: Background: The SarQoL® questionnaire was specifically designed to measure quality of life (QoL) in sarcopenia. Frailty and sarcopenia have areas of overlap, notably weak muscle strength and slow gait speed, which may mean that the SarQoL could provide a measure of QoL in frailty. This study aimed to evaluate the clinimetric properties of the SarQoL questionnaire in physical frailty using the Fried criteria. Methods: Analyses were carried out on data from the Sarcopenia and Physical impairment with advancing Age study. Frailty was assessed with the Fried criteria and QoL with the SarQoL, the Short‐Form 36‐Item, and the EuroQoL 5‐Dimension (EQ‐5D) questionnaires. We evaluated discriminative power (with the Kruskal–Wallis analysis of variance test), internal consistency (with Cronbach's alpha), construct validity (through hypotheses testing), test–retest reliability (with the intraclass correlation coefficient), measurement error (calculating standard error of measurement and smallest detectable change), and responsiveness (through hypotheses testing and standardized response mean). Results: In total, 382 participants were included for the validation and 117 for the responsiveness evaluation. They had a median age of 73 (69–79) years, took 5 (3–8) drugs, and had 4 (3–5) co‐morbidities. There were more women ( n  = 223; 58.4%) than men and, in total, 172 (45%) robust, 167 (44%) pre‐frail, and 43 (11%) frail participants. Discriminative power was confirmed when significantly lower ( P  < 0.001) overall SarQoL scores, and thus also worse QoL, were observed between robust [77.1 (64.35–85.90)], pre‐frail [62.54 (53.33–69.57)], and frail [49.99 (40.45–56.06)] participants. Six of the SarQoL domains performed likewise, with significantly lower scores according to frailty status with Domain 7 (fears) being the exception. Internal consistency was good ( α  = 0.866). Convergent (using Short‐Form 36‐Item and EQ‐5D) and divergent construct validity (using EQ‐5D) was confirmed. Test–retest reliability was excellent [intraclass correlation coefficient = 0.918 (0.834–0.961)], with a standard error of measurement of 3.88 and a smallest detectable change of 10.76 points. We found moderate responsiveness when five of the nine hypotheses were confirmed, coupled with a large effect size for the overall SarQoL score (corrected standardized response mean of −1.44). Conclusions: The SarQoL questionnaire has adequate clinimetric properties for use with frail patients in clinical practice and trials and could provide data that are more appropriate and detailed than the generic questionnaires currently used.